Self-expanding vs. balloon-expandable transcatheter heart valves in small aortic annuli - Kornyeva, Anastasiya; Burri, Melchior; Lange, Rüdiger; Ruge, Hendrik (Frontiers in Cardiovascular Medicine, 2023)
Clinical consequences of prosthesis-patient mismatch (PPM) after transcatheter aortic valve replacement (TAVR) is currently in the focus of clinical research. Patients with small aortic annulus are at higher risk to display PPM. Data on incidence and clinical consequences of PPM after TAVR with either balloon-expandable (BEV) or self-expanding (SEV) transcatheter heart valves in small aortic annulus is sparse. Patients with small aortic annulus (perimeter <72mm or aortic annulus area <400 mm2) who underwent BEV or SEV with contemporary transcatheter heart valve types were identified from the institutional TAVR database. Propensity score matching was applied for imbalanced baseline characteristics between patients undergoing BEV or SEV. Echocardiography and clinical follow-up up to 12 months was reported following VARC-3 recommendations. The primary endpoint was the incidence of pre-discharge PPM and its association to 1-year mortality. From a total of 507 patients with small aortic annulus, 192 matched patient-pairs with SEV or BEV were identified. Mean age was 81±7 (SEV) vs 81±6 (BEV) years (p=0.5), aortic annulus perimeter 69±3 mm vs.69±3 mm, (p=0.8), annulus area 357±27mm2 vs.357±27mm2, (p=0.8) and EuroScore II 5.8±6.6 vs.5.7±7.2 (p=0.9). SEV resulted in less moderate (20% vs.31%, p<0.001) and severe pre-discharge PPM (9% vs.18%, p<0.001) compared to BEV. At discharge (7±4 mmHg vs. 12±9 mmHg, p=0.003) and at 1-year (7±5 mmHg vs.13±3 mmHg, p<0.001) SEV displayed lower mean gradients compared to BEV. 30-day (6% vs 2%, p=0.07) and 1-year mortality (15% vs. 13%, p=0.07) were similar in SEV and BEV. Body surface area (OR: 1.35, p<0.001), implantation of BEV (OR: 3.32, p<0.001) and absence of postdilatation (OR: 2.16, p<0.001) were independent risk factors for any PPM. Moderate or severe PPM was not associated to 1-year mortality (OR: 0.98 p=0.96). The higher incidence of post-BEV PPM was not associated to 1-year mortality. However, lower mean gradients were obtained with SEV in patients with small aortic annulus.